Variation of M2+ (Ni and Zn) in Cellulose-based M2+/Cr Composite Materials to Determine Adsorption and Regeneration Abilities on Phenol Removal - Alfan Wijaya; Tarmizi Taher; Aldes Lesbani; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2022)
Cellulose-based Ni/Cr (Ni/Cr-C) and cellulose-based Zn/Cr (Zn/Cr-C) composite materials have been successfully carried out, which is indicated by the XRD, FTIR, and BET analysis. Layered double hydroxide Ni/Cr (Ni/Cr-LDH) increased surface area from 0.128 m2/g to 2.207 m2/g in Ni/Cr-C composites, and layered double hydroxide Zn/Cr (Zn/Cr-LDH) also increased surface area from 0.133 m2/g to 3.714 m2/g in Zn/Cr-C composites. The pHpzc of the material in this study is pH 5.94-8.43, while the optimum pH of all materials is pH 9. Ni/Cr-LDH experienced an increase in adsorption capacity after becoming a Ni/Cr-C composite, from 8.985 mg/g to 24.510 mg/g, and Zn/Cr-LDH experienced an increase in adsorption capacity from 13.263 mg/g to 30.960 mg/g in Zn/Cr-C. Zn/Cr-C composite material has a greater adsorption ability than Ni/Cr-C. Kinetic and isotherm model in this study followed by PSO kinetic with optimum contact time at 70 minutes and Freundlich isotherm. Ni/Cr-C and Zn/Cr-C composite materials can be used repeatedly in the regeneration process until the 4th cycle.